Enhancing Anti-Corruption Literacy and Strengthening the Strategic Role of Youth Organizations in Government Oversight in Serang City - Mahpudin Mahpudin; Rahmi Hidayati (Jurnal Pemberdayaan Masyarakat, 2025)
This community services initiative aims to enhance anti-corruption literacy and strengthen the role of youth organizations in overseeing governance in Serang City. The program is motivated by the high incidence of corruption cases in the public sector and the low level of civic participation, particularly among young people, in monitoring government performance. The implementation method comprises three stages: preparation, execution, and evaluation. The outreach materials cover fundamental concepts of corruption, the role of youth in participatory oversight, regulations on public information transparency, and the utilization of digital reporting platforms such as Jaga.id. The activity involved 20 participants from UNTIRTA and UIN SMH Banten, all of whom are members of KAMMI Banten. Evaluation results indicate a significant improvement in participants' understanding, with the proportion of participants categorized as having "excellent" knowledge increasing from 10% in the pre-test to 50% in the post-test. These findings demonstrate that a literacy-based outreach approach, combined with interactive discussions, is an effective way to foster anti-corruption awareness. This initiative is expected to serve as a replicable model for youth empowerment, promoting participatory oversight and the establishment of transparent and accountable governance. Beyond its local significance, the novelty of this article lies in demonstrating how community-based anti-corruption literacy programs, anchored in youth participation and digital engagement, can contribute to the global discourse on civic education and integrity systems. By providing empirical evidence from Indonesia, this study enriches international scholarship on anti-corruption strategies, particularly in illustrating how grassroots initiatives can complement formal governance reforms.